The perspectives of users of antiretroviral therapy on structural barriers to adherence in South Africa - A. Kagee; J. Nothling; B. Coetzee (South African Family Practice)
Background: The effectiveness of antiretroviral therapy (ART) and the importance of adherence to treatment regimens are widely known. Yet, suboptimal adherence to ART and retention in care of patients still persists and, by many accounts, is fairly widespread. The aim of this study was to identify the structural barriers that influenced adherence among patients who were enrolled in the national ART programme in South Africa.